Chemical polishing of InAs, InSb, GaAs and GaSb - Levchenko, I.V.; Tomashyk, V.M.; Stratiychuk, I.B.; Malanych, G.P.; Stanetska, A.S.; Korchovyi, A.A. (Functional Materials, 2017)
The mechanism and kinetics of chemical dissolution of InAs, InSb, GaAs and GaSb in (NH₄)₂Cr₂O₇-HBr-C₄H₆O₆ etching mixtures have been studied. Influence of tartaric acid on the parameters of chemical-dynamic polishing and morphology of the obtained crystals surface has been determined. Using of (NH₄)₂Cr₂O₇-HBr-C₄H₆O₆ etching solutions provides the controlled removal of thin layers and the polishing of investigated semiconductors. The polishing etchant compositions have been proposed and conditions for the chemical-dynamic polishing of the InAs, InSb, GaAs and GaSb crystals have been optimized.